Effects of O2 addition on the discharge parameters and production of reactive species of a transferred atmospheric pressure plasma jet - Nascimento, Fellype [UNESP]; Petroski, Kleber [UNESP]; Kostov, Konstantin [UNESP] (MDPI, 2021)
The therapeutic effects of atmospheric pressure plasma jets (APPJs) have been associated with the presence of reactive species, mainly the reactive oxygen and nitrogen ones, generated in this kind of plasmas. Due to that, many studies attempting to enhance the production of reactive species in APPJs have been performed. The employment of gas admixtures, usually mixing a noble gas with oxygen (O2) or water vapor, is one of the most common methods to achieve such goal. This work presents a study of how the addition of small amounts of O2 affects the electrical parameters and the production of reactive species in a transferred APPJ produced at the tip of a long and flexible plastic tube. The study was carried out employing helium (He) as the working gas and applying a high voltage (HV) in the form of amplitude-modulated sine waveform (burst mode). With this configuration it was possible to verify that the O2 addition reduces the discharge power and effective current, as a result of late ignition and shorter discharge duration. It was also found that the addition of O2 to a certain content in the gas admixture makes the light emission from oxygen atoms increase, indicating an increment in oxygen related reactive species in the plasma jet. However, at the same time the light emitted from hydroxyl (OH) and nitric oxide (NO) exhibits the opposite behavior, i.e., decrease, indicating a reduction of such species in the APPJ. For these reasons, the addition of O2 to the working gas seems to be useful for increasing the effectiveness of the plasma treatment only when the target modification effect is directly dependent on the content of atomic oxygen.
Keywords: DBD plasma; Plasma jets; Plasma properties; Reactive species; RONS